Serum D-dimer as an indicator of immediate mortality in patients with in-hospital cardiac arrest. Issue 143 (July 2016) - Deng, Yushuang; He, Lanying; Yang, Juan; Wang, Jian
Abstract: Introduction: Blood coagulation and fibrin activation with impaired fibrinolysis occurs not only during cardiac arrest (CA) but also after the return of spontaneous circulation (ROSC). The aim of the present study was to investigate the prognostic marker of immediate mortality prediction in in-hospital cardiac arrest (IHCA), with special attention to the serum D-dimer concentration. Methods: Retrospective chart review. Adult patients subjected to IHCA with resuscitation in the medical intensive care unit (ICU) from January 2012 to July 2015 were enrolled. Information about patient baseline characteristics, resuscitation characteristics, biochemical parameters and outcome details were collected. Logistic regression analysis was calculated to identify independent predictors for mortality. Receiver operating characteristic (ROC) curves were utilized to evaluate the accuracy of predictors. Results: Of the studied 192 patients (115 men, mean age 64.98 ± 17.66 years), more than half-part patients died immediately after resuscitation (118/192, 61.46%). The patients who failed to resuscitate had more often had a history of septicemia (15.25% vs 2.7%, p = 0.006), renal insufficiency (38.14% vs 14.86%, p = 0.001), pneumonia (51.69% vs 33.78%, p = 0.015) and less often had an initial shockable rhythm (16.1% vs 29.73%, p = 0.019) than those who sustained ROSC. Pre-CA serum D-dimer concentration was significantly higher in the death group than that in ROSC group (22.48 ± 17.66 vs 9.49 ± 9.09 mg/L, p < 0.0001). On multivariate logistic regression analysis, D-dimer (odds ratios, 1.07, 95% confidence interval 1.02 to 1.13) was an independent predictor of mortality. Conclusions: Serum D-dimer serves as a useful indicator of immediate mortality after resuscitation in patients with IHCA. Highlights: 1. Serum D-dimer concentration increases early before CA. 2. Pre-CA D-dimer level associates to early resuscitation outcome. 3. Serum D-dimer serves as a useful indicator of immediate mortality after resuscitation in patients with IHCA.